Effect of stroke drills on intra-cycle hip velocity in front crawl - Arellano, R.; Dominguez-Castells, R.; Perez-Infantes, E.; Sanchez, E. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Current teaching and competitive swimming programs are composed by a proper combination of skill acquisition and conditioning exercises. Many swimming books or papers described or classified these swimming exercises proposing guidelines to use them properly or in a skill assessment context. While hip or centre of mass intra-cycle velocity has been studied in the current competitive strokes using observational or biomechanical methods this has not been the case with the stroke drills applied to teach or to train the swimming technique. A first attempt was performed analyzing the differences on body rotation and 3D hand swimming path between freestyle swimming and one arm crawl stroke drills (López, Gutiérrez, & Arellano, 2002). Less body rotation and hand depth were found during the practice of formal one-arm and catch-up crawl stroke, while a modified one-arm stroke drill obtained similar values to that recorded during no breathing freestyle swimming.The purpose of this study is to reveal the differences in intra-cycle hip velocity between formal front crawl and four other front crawl swimming coordination drills. METHODS: Thirteen national and regional level swimmers (five males and eight females, aged 19.58±2.23) participated in this study as volunteers. Each stroke drill was defined as: a) No-breathing formal freestyle swimming (reference technique); b) Crawl catch-up stroke, kicking some seconds after each stroke; c) One arm front crawl with the resting arm extended in front, breathing on the arm-moving side; d) One arm front crawl with the resting arm close to the body, breathing on the no-moving side; e) Controlled two-arm freestyle, kicking some seconds after each stroke, with one arm resting close to the body and the second one resting extended in front. RESULTS: Mean 25m velocity (m/s) a) 1.64; b) 1.10*; c) 1.08*; d) 1.07*; e) 1.00*. Mean % 2nd peak a) 69.9; b) 76.9; c) 38.1 ; d) 80.9 ; e) 69.0 [all n.s.] Mean 2nd peak a) 2.06; b) 1.41*; c) 1.38* ; d) 1.14* ; e) 1.26* * p<0.01 between a) and b), c), d) and e) CONCLUSIONS: The freestyle stroke drills applied to teach or train different types of interlimb coordination reduce the mean and peak value of the intra-cycle hip velocity while the percentage location of peak hip-velocity value during the underwater stroke phase is kept similar without significant statistical differences.